2015
DOI: 10.1097/ta.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

National mandatory motorcycle helmet laws may save $2.2 billion annually

Abstract: Economic analysis, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…5 This fact is of concern, given that wearing a crash helmet can reduce the risk of head and brain injuries and the risk of death. Analysis of the cost of hospitalization of motorcyclists who did not wear crash helmets in the United States showed that it reached approximately US$2.2 billion dollars in 2010; 15 while one billion dollars a year could be saved if all motorcyclists in that country wore a crash helmet. 16 Increased law enforcement could be a considerably effective means of reducing this risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…5 This fact is of concern, given that wearing a crash helmet can reduce the risk of head and brain injuries and the risk of death. Analysis of the cost of hospitalization of motorcyclists who did not wear crash helmets in the United States showed that it reached approximately US$2.2 billion dollars in 2010; 15 while one billion dollars a year could be saved if all motorcyclists in that country wore a crash helmet. 16 Increased law enforcement could be a considerably effective means of reducing this risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…States without universal helmet laws have been shown to have a greater health care expenditure because of the nature of injuries sustained and level of hospital care required by unhelmeted riders. 18 Literature has consistently shown a strong trend toward increased use of public funds for uninsured, unhelmeted patients. 7,14,18 Helmet use has shown to decrease the mean hospitalization cost by more than $6000 per patient.…”
Section: Universal Helmet Laws: a State Of The Unionmentioning
confidence: 99%
“…18 Literature has consistently shown a strong trend toward increased use of public funds for uninsured, unhelmeted patients. 7,14,18 Helmet use has shown to decrease the mean hospitalization cost by more than $6000 per patient. 2 Iowa, a state with no helmet laws, has indicated cost savings of up to $20,000 per helmeted patient.…”
Section: Universal Helmet Laws: a State Of The Unionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of helmets can significantly reduce the severity of head injuries in an accident (11,12). Although helmets are regarded as an important savior for motorcyclists at the time of an incident, studies in different countries like China, Malaysia, Vietnam, Thailand, India, Pakistan, Iran, Nigeria, Argentina, Italy and some states of the United States (US) have reported that only a low rate of motorcyclists wear helmets (6,13,14). In Iran, the rates of using helmets for the riders and the passengers are 35 percent and 12 percent, respectively (7).…”
Section: Introductionmentioning
confidence: 99%